The Therapeutic Effect of STAT3 Signaling-Suppressed MSC on Pain and Articular Cartilage Damage in a Rat Model of Monosodium Iodoacetate-Induced Osteoarthritis - Seon-yeong Lee; Seung Hoon Lee; Hyun Sik Na; Ji Ye Kwon; Goo-Young Kim; KyungAh Jung; Keun-Hyung Cho; Seon Ae Kim; Eun Jeong Go; Min-Jung Park; Jin-Ah Baek; Si Young Choi; et al. (Frontiers in Immunology, 2018)
Osteoarthritis (OA) is a degenerative disease that induces pain, cartilage deformation, and joint inflammation. Mesenchymal stem cells (MSCs) are potential therapeutic agents for treatment of OA. However, MSC therapy can cause excessive inflammation. Signal transducer and activator of transcription 3 (STAT3) modulates secretion of many proinflammatory cytokines. Experimental OA was induced by intra-articular (IA) injection of monosodium iodoacetate (MIA) to the right knee of rats. MSCs from OA patients (OA-MSCs) were treated with STA21, a small molecule that blocks STAT3 signaling, by IA or intravenous (IV) injection after MIA injection. Pain severity was quantified by assessment of secondary tactile allodynia using the von Frey assessment test. Cartilage degradation was measured by microcomputed tomography image analysis, histological analysis, and the Mankin score. Protein and gene expression was evaluated by enzyme-linked immunosorbent assay, immunohistochemistry, and real-time polymerase chain reaction. MSCs increased production of proinflammatory cytokines under inflammatory conditions. STA21 significantly decreased expression of these proinflammatory molecules via inhibition of STAT3 activity but increased gene expression of molecules related to migration potential and immunomodulation in OA-MSCs. STAT3-inhibited OA-MSCs administrated by IV or IA injection decreased pain severity and cartilage damage in rats with MIA-induced OA rats by decreasing proinflammatory cytokines in the joints. Combined IA and IV-injected STAT3-inhibited OA-MSCs had an additive effect of pain relief in MIA-induced OA rats. STAT3 inhibition may optimize the therapeutic activities of MSCs for treating OA by attenuating pain and progression of MIA by inhibiting inflammation and cartilage damage.